Body mass index and cardiorenal outcomes in the EMPEROR-Preserved trial: principal findings and meta-analysis with the DELIVER trial - Sattar, Naveed; Butler, Javed; Lee, Matthew M.Y.; Harrington, Josephine; Sharma, Abhinav; Zannad, Faiez; Filippatos, Gerasimos; Verma, Subodh; Januzzi, James L.; Ferreira, João Pedro; Pocock, Stuart J.; Pfarr, Egon; et al. (European journal of heart failure, 2024)
Aims Both low and high body mass index (BMI) are associated with poor heart failure outcomes. Whether BMI modifies benefits of sodium-glucose cotransporter 2 inhibitors (SGLT2i) in heart failure with preserved ejection fraction (HFpEF) requires further investigation. Methods and results Using EMPEROR-Preserved data, the effects of empagliflozin versus placebo on the risks for the primary outcome (hospitalization for heart failure [HHF] or cardiovascular [CV] death), change in estimated glomerular filtration rate (eGFR) slopes, change in Kansas City Cardiomyopathy Questionnaire clinical summary score (KCCQ-CSS), and secondary outcomes across baseline BMI categories (<25 kg/m2, 25 to <30 kg/m2, 30 to <35 kg/m2, 35 to <40 kg/m2 and ≥40 kg/m2) were examined, and a meta-analysis conducted with DELIVER. Forty-five percent had a BMI of ≥30 kg/m2. For the primary outcome, there was a consistent treatment effect of empagliflozin versus placebo across the BMI categories with no formal interaction (p trend = 0.19) by BMI categories. There was also no difference in the effects on secondary outcomes including total HHF (p trend = 0.19), CV death (p trend = 0.20), or eGFR slope with slower declines with empagliflozin regardless of BMI (range 1.12-1.71 ml/min/1.73 m2 relative to placebo, p trend = 0.85 for interaction), though there was no overall impact on the composite renal endpoint. The difference in weight change between empagliflozin and placebo was −0.59, −1.48, −1.54, −0.87, and − 2.67 kg in the lowest to highest BMI categories (p trend = 0.016 for interaction). A meta-analysis of data from EMPEROR-Preserved and DELIVER showed a consistent effect of SGLT2i versus placebo across BMI categories for the outcome of HHF or CV death. There was a trend toward greater absolute KCCQ-CSS benefit at 32 weeks with empagliflozin at higher BMIs (p = 0.08). Conclusions Empagliflozin treatment resulted in broadly consistent cardiac effects across the range of BMI in patients with HFpEF. SGLT2i treatment yields benefit in patients with HFpEF regardless of baseline BMI.